Outage Analysis of Relay-Assisted mmWave Cellular Systems Employing JSDM - Jun Chen; Deli Qiao; Haifeng Qian (IEEE Access, 2019)
In this paper, the outage probabilities of relay-assisted millimeter wave (mmWave) cellular systems employing joint spatial division and multiplexing (JSDM) are investigated. It is assumed that the macro base station (BS) equipped with a large number of antennas serves the single antenna relay and users simultaneously and that the relay is located at the edge of the macro cell. Theoretical analysis of the signal-to-interference-plus-noise ratio (SINR) outage probabilities of each user with and without the second stage precoding is first obtained, respectively. The cell SINR outage probabilities are then derived. Under the noise-limited assumption, simplified closed-form expressions of the outage probabilities are given as well. The simulation results demonstrating the performance improvement due to the relay are provided. Overall, the impact of deploying a relay in the mmWave cellular systems on the outage probabilities is characterized.